Are Recent Generations Catching Up or Falling Behind? Trends in Inter-Generational Inequality - Michael Freedman (Luxembourg Income Study (LIS), 2017)
Recent work has shown that inequalities between generations are most pronounced in the conservative European welfare states, and that these trends are less pronounced in social democratic and liberal welfare states (Chauvel and Schroder 2014). However, it is likely that across all advanced capitalist societies superior earnings opportunities and steady employment are pursued at a later age for recent generations due to several interconnected lifestyle changes. In this paper, I examine the variation in generational inequalities across different regimes, with a focus on recent cohorts. For the analysis, I use data from the Luxembourg Income Study (LIS). The repeated cross-sectional data allow me to trace the generational changes in income opportunities for 8 countries, using both Age-Period-Cohort-Detrended coefficients (APCD) and synthetic cohort models. My results suggest that for most countries, cohorts born after 1970 have experienced fewer earning opportunities, relative to cohorts born between 1950 and 1970. Moreover, these generational inequalities have been more pronounced in the coordinated political economies, and less pronounced in the liberal political economies. However, synthetic cohort models suggest that while recent generations have suffered from successively worse entry positions, they appear to be 'catching up', which suggests that lifelong 'scarring effects' may not be inevitable.
Keywords: 330